Korean perspectives of nasopharynx cancer management - Ahn, Yong Chan; Kim, Yeon Sil (Chinese Clinical Oncology; Vol 5, No 2 (April 19, 2016): Chinese Clinical Oncology (Nasopharyngeal Carcinoma-Guest Editors: Joseph Wee, Yoke-Lim Soong, Melvin Chua), 2016)
Though Korea is located in non-endemic region of Epstein-Barr virus (EBV) infection and the incidence rate of nasopharynx cancer (NPCa) is very low, some clinical and histologic characteristics are similar to those in EBV endemic regions. Korean Radiation Oncology Group (KROG) established a database of NPCa patients and a few informative studies were performed, which mostly have conformed to those from the previously reports by others. Large variation in intensity modulated RT (IMRT) detail was recognized and the key principles at Samsung Medical Center are introduced. Based on the current understandings of Korean perspective, further refinement aiming at improved clinical outcomes would be anticipated through large scale prospective clinical trials.